2021
DOI: 10.3389/fonc.2021.737938
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Imaging With Indocyanine Green for the Treatment of Endometriosis: Results From the Gre-Endo Trial

Abstract: IntroductionA current challenge for endometriosis surgery is to correctly identify the localizations of disease, especially when small or hidden (occult endometriosis), and to exactly define their real extension. The use of near-infrared radiation imaging (NIR) after injection of indocyanine green (ICG) represents one of the most encouraging method. The aim of this study is to assess the diagnostic value of NIR-ICG imaging in the surgical treatment of endometriosis compared with the standard of treatment.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Turco. et al [33] compared the diagnostic e ciency of conventional WL imaging to ICG imaging during 51 patients with EMs and found that ICG imaging alone and combined with WL imaging showed good results in the intraoperative detection rate of EMs. These inconsistent results make the diagnostic value of ICG imaging uncertain, through the quantitative synthesis of existing homogeneous results can provide more reliable conclusions, this is the main purpose of the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Turco. et al [33] compared the diagnostic e ciency of conventional WL imaging to ICG imaging during 51 patients with EMs and found that ICG imaging alone and combined with WL imaging showed good results in the intraoperative detection rate of EMs. These inconsistent results make the diagnostic value of ICG imaging uncertain, through the quantitative synthesis of existing homogeneous results can provide more reliable conclusions, this is the main purpose of the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has high progestational and mild anti-gonadotrophic effects [26][27][28][29]. A previous randomized clinical study shows that oral dienogest reduces pelvic discomfort in women with endometriosis better than in a placebo [6,[30][31][32]. Dienogest was shown to be similarly effective in reducing pelvic pain in clinical studies that compared oral dienogest with gonadotropinreleasing hormone (GnRH) agonists for 16 weeks or 24 weeks in women with endometriosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, as an objective, non-invasive and real-time approach, near infrared imaging has attracted much attention [23][24][25][26]. Previous studies have shown that it has been broadly used in lymphangiography, angiography, sentinel lymph nodes, tumor margin detection and so on [27][28][29].…”
Section: Discussionmentioning
confidence: 99%